Disqualification of Company Directors: Safeguarding the Public Interest in the Kenyan Investment Market - Mwaura, Kiarie (Journal of Law and Commerce, 2019)
Over the last two decades, Africa has gone through tremendous economic transformation. It was only in 2004 when the Prime Minister for the UK, Tony Blair, described Africa as the “scar on the conscience of the world” when he was establishing the Commission for Africa. A decade later, he described Africa as “the most exciting continent on the planet because of its opportunities.” Within less than twenty years, the continent has become the world’s most rapidly growing economic region. This economic growth has been attributed largely to the active private sector. Kenya, for example, has realized the highest growth rate in the East African region due to its private sector, which makes a major contribution to the country’s GDP. For this growth rate to continue, African countries need to create competitive legal frameworks that continue to attract investors and protect their interests. One of such is the disqualification framework for company directors that seeks to protect the public by placing a prohibition on a miscreant director from being involved, for a specific period, in the management of companies. An efficient disqualification framework also prevents people without the necessary qualifications from managing companies and deters those who might be tempted to engage in fraudulent activities. Without a strict disqualification framework, investors are unlikely to be attracted to a country, as they risk losing their investments when their companies are managed by incompetent, negligent, or fraudulent directors, especially those with a track record of mismanaging other companies. This philosophy was captured clearly by the Kenyan Government when it enacted the Companies Act 2015 and stated that one of its key objectives was to facilitate commerce, industry, and other socio-economic activities. It is against this backdrop that this Article examines whether the disqualification framework under the Companies Act 2015 is adequate to protect the interests of investors. This framework is contrasted with the one that existed under the repealed Companies Act 1962 with a view to assessing whether the reforms are likely to bring about the desired changes.